Extraction and Elucidation of the Components of the Philosophical Foundations of Environmental Education at the Upper Secondary Level - Tanouri, Alireza; Gholtash, Abbas; Mashinchi, Aliasghar (Assessment and Practice in Educational Sciences, 2026)
The environment is in a critical condition, and education and training are essential to address its challenges. The purpose of this study is to extract and elucidate the components of the philosophical foundations of environmental education in order to propose a model for upper secondary education. The research employed a qualitative approach, utilizing meta-synthesis and theoretical inference methods. This study examined sources and articles related to the philosophical foundations of environmental education and used purposive sampling to collect data. The data collection instrument consisted of coding sheets, and data analysis was conducted using thematic analysis. The findings indicate that the educational model of environmental education comprises ontological, anthropological, epistemological, and axiological components. In addition, objectives such as the development of environmental ethics, the growth of spirituality, and the enhancement of environmental culture were identified as key outcomes of the study. Fundamental principles include viewing humans as stewards of nature, environmental justice, and coexistence. Instructional methods encompass education grounded in Islamic foundations, participation and experiential learning, critical thinking, and knowledge-based approaches. Ultimately, the study demonstrates that the success of environmental education at the upper secondary level depends on the institutionalization of philosophical components within an operational model that cultivates a generation that is conscious of and committed to ecosystem sustainability.